A flame retardant sandwiched separator coated with ammonium polyphosphate wrapped by SiO2 on commercial polyolefin for high performance safety lithium metal batteries. (December 2020) - Liao, Can; Wang, Wei; Han, Longfei; Mu, Xiaowei; Wu, Na; Wang, Junling; Gui, Zhou; Hu, Yuan; Kan, Yongchun; Song, Lei
Highlights: A facile but effective approach of coating is introduced to prepare advanced sandwiched separator. The sandwiched separator with absorbing electrolyte shows excellent flame retardant property. Thermal stability, ionic conductivity and electrochemical performances have been improved. The sandwiched separator has excellent capability to inhibit lithium dendrites. Abstract: Lithium metal batteries are regarded as the "Holy Grail" among varieties of energy storage systems. Nevertheless, the development and practical application of lithium metal batteries have been seriously hindered by the safety issues, which are generated from threatening lithium dendrites, flammable separator and electrolytes. In this work, a flame retardant sandwiched separator has been prepared by simply coating ammonium polyphosphate wrapped by SiO2 (APP@SiO2 ) on the surface of commercial polyolefin, thus significantly improving the safety of lithium metal batteries. The APP@SiO2 separator impregnated with sufficient electrolyte exhibits excellent flame retardant performance, which manifests self-extinguishing performance. In addition, thermal stability, ionic conductivity, and electrochemical performances have been also improved obviously. More importantly, the APP@SiO2 separator possesses a satisfactory ability to suppress lithium dendrites, owing to the fact that the high ionic conductivity of modified separator can promote uniform deposition of Li + and the dangerous lithium dendrites contacted with separator are consumed by the reaction with SiO2 . Therefore, a facile but effective approach can endow the multifunctional sandwiched separator with a favorable potential application for high performance and safety lithium metal batteries. Graphical abstract: Image, graphical abstract